ØªÙ†ÙÙŠØ¯ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¬Ù„Ø³ Ø¯Ø§Ø± Ø§Ù„Ø®ÙŠØ±Ø§Øª Ø¬Ù…Ø¨Ø± - Abicandra, Muh. Nidom Hamami; Saadah, Zuroatus (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Ù…Ù„Ø®Øµ Ø§Ù„Ø¨ØØ« ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ÙˆØµÙ ÙƒÙŠÙ ÙŠÙƒÙˆÙ† ØªÙ†ÙÙŠØ° ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¬Ù„Ø³ Ø¯Ø§Ø± Ø§Ù„Ø®ÙŠØ±Ø§Øª Ø¬Ù…Ø¨Ø±. ÙˆÙˆØµÙ Ø§Ù„Ø¹ÙˆØ§Ù…Ù„ Ø§Ù„ØªÙŠ ÙŠÙ†Ø¬Ø Ø¨Ù‡Ø§ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ…Ø¹ÙˆÙ‘Ù‚Ø§ØªÙ‡ ÙÙŠ Ù…Ø¬Ù„Ø³ Ø¯Ø§Ø± Ø§Ù„Ø®ÙŠØ±Ø§Øª Ø¬Ù…Ø¨Ø± . Ø£Ù…Ø§ Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙÙ‡Ùˆ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙƒÙŠÙÙŠ Ø§Ù„ÙˆØµÙÙŠ. ÙˆÙ†ÙˆØ¹ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…ÙŠØ¯Ø§Ù†ÙŠ. ÙˆÙ…ØµØ§Ø¯Ø± Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ù…Ø¯Ø±Ø³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ùˆ Ø§Ù„Ø±Ø¦ÙŠØ³Ø© Ø§Ù„Ù…Ø¬Ù„Ø³ ÙˆØ£Ø¹Ø¶Ø§Ø¡ Ø§Ù„Ù…Ø¬Ù„Ø³. ÙˆØ·Ø±ÙŠÙ‚Ø© Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù‡ÙŠ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ø§Ù„Ø´Ø®ØµÙŠØ© ÙˆØ§Ù„ÙˆØ«Ø§Ø¦Ù‚ÙŠØ©. ÙˆØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…ÙŠÙ„Ø³ ÙˆÙ‡ÙˆØ¨Ø±Ù…Ø§Ù† Ù‡Ùˆ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØªØ®ÙÙŠØ¶ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØ¹Ø±Ø¶ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØ§Ø³ØªÙ†ØªØ§Ø¬ Ø§Ù„Ø¨ØØ«. ÙˆØµØØ© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ«Ù„ÙŠØ« Ø§Ù„Ø£Ø¯Ø§ÙˆØ§Øª. ÙŠÙƒÙˆÙ† ØªÙ†ÙÙŠØ° Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¬Ù„Ø³ Ø¯Ø§Ø± Ø§Ù„Ø®ÙŠØ±Ø§Øª Ø¬Ù…Ø¨Ø±. Ø¹Ù„Ù‰ Ø£Ù† ØªÙ†ÙÙŠØ° Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¬Ù„Ø³ Ø¯Ø§Ø± Ø§Ù„Ø®ÙŠØ±Ø§Øª Ø¨Ø§Ù„Ø®Ø·ÙˆØ§Øª Ø§Ù„ØªÙ†ÙÙŠØ° Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù†Ù‡Ø§ ØªØ®Ø·ÙŠØ· Ø§Ù„ØªÙ†ÙÙŠØ° Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆÙÙŠÙ‡ Ø§Ù‡Ø¯Ø§Ù Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ùˆ Ø§Ù„Ù…Ø§Ø¯Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„ØªÙ‚ÙˆÙŠÙ… Ø§Ù„ØªØ¹Ù„ÙŠÙ…. ÙˆØ£Ù…Ø§ ØªÙ†ÙÙŠØ° Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù‡Ùˆ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ØªØ¹Ù„Ù… Ù…Ø·Ø§Ø¨Ù‚ Ø¨Ø§Ù„Ø®Ø·ÙˆØ§Øª Ø§Ù„ØªÙ†ÙÙŠØ° Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù†Ù‡Ø§ Ø§Ù„Ø¥ÙØªØªØ§ØØŒ ÙŠÙØªØ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø¨Ø§Ø§Ù„Ø³Ù„Ø§Ù… ÙˆØ§Ø³ØªØ®Ø¨Ø± Ø§Ù„ØØ§Ù„ Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª ÙˆÙŠÙƒØ±Ø± Ø§Ù„Ø£Ø³ØªØ§Ø° Ø§Ù„Ù…Ø§Ø¯Ø© Ø§Ù„ØªÙŠ Ù‚Ø¯ ØªØ¹Ø·Ù‰ ÙÙŠ Ù…Ù‚Ø§Ø¨Ù„Ø© Ø§Ù„Ù…Ø§Ø¶Ù‰ Ù„ÙƒÙŠ ÙŠØ°ÙƒØ±ÙˆÙ† Ø¹Ù† ØªÙ„Ùƒ Ø§Ù„Ù…Ø§Ø¯Ø©. ÙˆÙŠÙƒÙˆÙ† Ø§Ù„Ø¹ÙˆØ§Ù…Ù„ Ø§Ù„ØªÙŠ ÙŠÙ†Ø¬Ø Ø¨Ù‡Ø§ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ…Ø¹ÙˆÙ‘Ù‚Ø§ØªÙ‡ ÙÙŠ Ù…Ø¬Ù„Ø³ Ø¯Ø§Ø± Ø§Ù„Ø®ÙŠØ±Ø§Øª Ø¬Ù…Ø¨Ø± Ù…Ù†Ù‡Ø§ : Ø§Ù„Ù…Ø¹Ù„Ù…ØŒ ÙˆØ§Ù„Ø·Ø§Ù„Ø¨Ø§ØªØŒ ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…. Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙØªØ§ØÙŠØ©: Ø§Ù„ØªÙ†ÙÙŠØ° ØŒ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Abstract This research aims to describe how the implementation of Arabic language instruction in the Dar al-Khairat Jember Council is. He described the factors that make Arabic language education successful and its obstacles in the Dar al-Khairat Jumper Council. As for the research method used in this research, it is the qualitative descriptive method. The type of research is field research. The research sources are the Arabic teacher, the council president, and the council members. The data collection method used is the observational, personal and documentary interview method. Data analysis using Mills and Hubermann is data collection, data reduction, data presentation, and research conclusion. Data validity using the toolbox triangulation approach. The implementation of Arabic language education in Dar Al Khairat Jember Council. That the implementation of the Arabic language education in the House of Good things is the implementation steps of education, including planning the implementation of education and it includes the objectives of education and the subject education and the method of education and means of education and evaluation of education. As for the implementation of education, it is the process of educated education in conformity with the implementation steps, including the opening, education opens in peace and the students are informed of the situation and the professor repeats the material that may be given in the last interview in order to mention that material. The factors in which the Arabic language education succeeds and its obstacles in the House of Charity Council are: the teacher, female students, and the means of education.